An exploration of the experiences of women with disabilities in a rural setting: the case of Insiza District, Zimbabwe - Tondori, Albert (My University, 2016)
This study aimed to explore the challenges experienced by women with disabilities in a rural setting, and the coping strategies they adopt in a time of economic crisis in Zimbabwe. The study made use of a qualitative exploratory design which necessitated the use of interviews (in-depth and semi-structured) and focus group discussions (FGDs) conducted in Insiza District, Matabeleland South Province in Zimbabwe. The study consisted of two different categories of participants which were: key informants (community leaders, government officials, non-governmental officials) as well as the subjects of the study who are women with disabilities. The study aimed to explore the experiences of rural women with disabilities. In this endeavour the study also illuminates how the economic crisis in Zimbabwe further constrains the already disadvantaged women with disabilities in a rural setting, who have to contend with multiple identities: being persons with disabilities, being poor women and inhabitants of a rural setting where resources are scarce, and being citizens of a country experiencing an economic downturn. The findings from the study were understood through the explanatory framework of the Capabilities Approach (CA). The study argues that the approach to disability in Zimbabwe is unsystematic, individualistic and paternalistic, thereby imposing upon women with disabilities multiple levels of oppression
A research report submitted to the department of Development Studies in partial fulfilment of the requirements for the degree of Master of Arts in Development Studies September 2016.
Keywords: Disabilities--Zimbabwe; Sociology of disability--Zimbabwe; Women--Zimbabwe